How the Customer Trust and Customer Satisfaction Mediate Brand Image and Service Quality on Customer Loyalty in Islamic Microfinance Institutions - Rosalina achmad; Nihayatu Aslamatis Solekah (Universitas Darussalam Gontor, 2022)
The purpose of this study was to determine the influence of brand image and service quality on customer loyalty through customer trust and customer satisfaction. This study used purposive sampling method with sample of 205 respondents. The analysis test used the statistical model Structural Equation Modeling-Partial Least Square (SEM-PLS). The results indicated that brand image had no direct influence on customer loyalty and service quality had direct influence on customer loyalty. Meanwhile, brand image and service quality had no indirect influence on customer loyalty through customer trust. This was because customer trust could not become mediating variable. But brand image had indirect influence on customer loyalty through customer satisfaction. That was because customer satisfaction could become perfect mediating variable. Meanwhile, service quality had no indirect influence on customer loyalty through customer satisfaction. This was because the direct influence value of service quality on customer loyalty was greater than the indirect influence. The implication was that customer loyalty could occur because of customer satisfaction, and customer satisfaction could occur because the institution had good brand image.